Odpowiedzi

2010-03-24T21:02:15+01:00
Pc=2Pp+Pb
Ppodstawy=a²√3/2
Pboczne=3aH

pierwszy przypadek gdzie
h=8
a=6

Pp=6²√3/2=36√3/2=18√3
Pb=3*6*8=144
Pc=2*18√3+144=36√3+144=36(√3+4)

drugi przypadek gdzie
h=6
a=8

Pp=8²√3/2=64√3/2=32√3
Pb=3*8*6=144
Pp=2*32√3+144=64√3+144=8(8√3+18)
2010-03-24T21:06:55+01:00
Pc= 2Pp + Pb
Pp=1/2*a*h
h=a pierwiastki z 3 / 2
h=6 pierwiastki z 3 / 2
h=3 pierwiastki z 3
Pp=1/2*6*3 pierwiastki z 3
Pp=9 pierwiastków z 3
Pb=a*b
Pb=8*6
Pb=48
3Pb=144
Pc=2*9 pierwiastków z 3 + 144
Pc=18 pierwiastków z 3 +144